Cooperative magnetophoresis of magnetic nanoparticles under hydrodynamic regime: Experimental and theoretical study - Wong, Yi Xuan (2023)

(untitled)
This project focuses on modelling of the magnetophoresis kinetics of magnetic nanoparticles (MNPs) under the cooperative and hydrodynamic regimes so that the understanding towards the transport mechanism of this separation process can be further enhanced. The study begins with the functionalization of MNPs with poly(sodium 4-styrenesulfonate) (PSS) at different mass ratios, with the aim to identify the optimal MNP to PSS mass ratio during the functionalization process to produce MNPs with the highest colloidal stability. Here, the MNP system functionalized under the MNP to PSS ratio of 1:1 is found to be exhibiting the highest colloidal stability among all MNP system produced in this study, hence, it is chosen as the model system to be used in the subsequent magnetophoresis experiments. According to the experimental results of the magnetophoresis kinetics measurement, the cooperative effect is found to be more apparent during the higher MNP concentration, in which the separation time reduced by 66 % when the MNP concentration is increased from 50 mg/L (separation time of 162 s) to 300 mg/L (separation time of 54 s). In addition, the hydrodynamic effect is also revealed to be dominating the magnetophoresis experiment that is conducted in this study due to the continuity homogeneity of the MNP solution throughout the entire timescale of the experiment, owing to the consistent agitation of induced convective current within the MNP solution. The final objective of this study is to develop a mathematical model that can predict the magnetophoresis kinetic profile under the simultaneous presence of both cooperative and hydrodynamic effects. The modelling was conducted by assuming the continuous homogeneity of the MNP solution (by incorporating the hydrodynamic effect) and occurrence of tip-to-tip aggregation (by incorporating the cooperative effect), which ix results in prediction results that are in good agreement with the experimental results. For instance, the model prediction is also showing a consistent trend in which the separation rate is more rapid for the magnetophoresis conducted under the higher MNP concentration. This study has successfully developed a mathematical model that is able to predict the magnetophoresis kinetics up to a good accuracy, which can be useful in the design of the low gradient magnetic separation in various industrial applications.